Owner assessment of chronic pain intensity and results of gait analysis of dogs with hip dysplasia treated with acupuncture - Teixeira, Lï¿½via R. [UNESP]; Luna, Stelio P. L. [UNESP]; Matsubara, Lï¿½dia M. [UNESP]; Cï¿½pua, Maria L. B. [UNESP]; Santos, Bianca P. C. R. [UNESP]; Mesquita, Luciane R. [UNESP]; Faria, Luis G. [UNESP]; Agostinho, Felipe S. [UNESP]; Hielm-Bjï¿½rkman, Anna (American Veterinary Medical Association (AVMA), 2016)
OBJECTIVE To evaluate pain intensity and kinetic variables in dogs with hip dysplasia (HD) treated with acupuncture, carprofen, or a placebo. DESIGN Randomized, controlled clinical study. ANIMALS 54 HD-affected dogs and 16 healthy dogs. PROCEDURES Seven HD-affected dogs were removed from the study. Dogs with HD were treated in a blinded manner for 30 days with acupuncture (once weekly for 5 sessions; n = 15), carprofen (4.4 mg/kg [2.0 mg/lb], PO, q 24 h; n = 16), or placebo capsules containing lactose (1 mg/kg [0.45 mg/lb], PO, q 24 h; n = 16). Dogs were evaluated 2 weeks and immediately before (baseline) and 2, 4, and 6 weeks after the onset of treatment. Owners evaluated the dogs’ pain intensity with 2 validated questionnaires and a visual analogue scale (VAS) for pain and evaluated degree of lameness with a VAS for locomotion. Kinetics of the hind limbs were also evaluated. Sixteen HD-free dogs were used to assess the evaluation protocol. RESULTS Owners’ assessments revealed that outcomes of the 3 treatments did not differ significantly. The Canine Brief Pain Inventory and VAS pain intensity assessments were decreased from baseline at weeks 4 and 6, respectively, but only in acupuncture-treated dogs. The locomotion VAS values were decreased at week 4 in acupuncture-treated and carprofen-treated dogs. Kinetic evaluation findings did not differ among the groups or over time. CONCLUSIONS AND CLINICAL RELEVANCE Neither acupuncture nor carprofen was significantly different from placebo. Acupuncture and carprofen reduced the degree of subjectively evaluated lameness, and acupuncture was associated with a decrease in validated chronic pain scores.